2020
DOI: 10.1101/2020.10.20.20215863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive deficits in people who have recovered from COVID-19 relative to controls: An N=84,285 online study

Abstract: Case studies have revealed neurological problems in severely affected COVID-19 patients. However, there is little information regarding the nature and broader prevalence of cognitive problems post-infection or across the full spread of severity. We analysed cognitive test data from 84,285 Great British Intelligence Test participants who completed a questionnaire regarding suspected and biologically confirmed COVID-19 infection. People who had recovered, including those no longer reporting symptoms, exhibited s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 19 publications
4
89
0
4
Order By: Relevance
“…Recently, Yu et al 55 reported that individuals suspected of having COVID-19 tend to adopt negative coping styles, receive less social support, and have low utilization rates of social support. Continuous forced isolation and uncertainty about their health status may lead to patients’ sensitivity, suspicion, fear, and cognitive deviation (such as emotional processing disorders 70 that could aggravate mental health problems). Individuals’ discernment of acquired information is important for their understanding of the correct protective measures against the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yu et al 55 reported that individuals suspected of having COVID-19 tend to adopt negative coping styles, receive less social support, and have low utilization rates of social support. Continuous forced isolation and uncertainty about their health status may lead to patients’ sensitivity, suspicion, fear, and cognitive deviation (such as emotional processing disorders 70 that could aggravate mental health problems). Individuals’ discernment of acquired information is important for their understanding of the correct protective measures against the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be relevant in the control of residual effects of COVID 19 disease. Indeed, in a recent study including 84,285 Great British Intelligence Test with biologically confirmed COVID-19 infection, people who had recovered, including those no longer reporting symptoms, exhibited significant cognitive deficits (69). The scale of the observed deficits was equivalent to the average 10-year decline in global performance between the ages of 20 to 70 within the same dataset.…”
Section: Melatonin and Sleepmentioning
confidence: 96%
“…In a recent study, to the present date (23 November 2020) published as a preprint, cognitive test data were obtained from 84,285 Great British Intelligence Test participants who completed a questionnaire regarding suspected and biologically confirmed COVID-19 infection [ 101 ]. People who had recovered, including those no longer reporting symptoms, exhibited significant cognitive deficits when controlling for age, gender, education level, income, racial-ethnic group, and pre-existing medical disorders.…”
Section: Melatonin and Neuroprotectionmentioning
confidence: 99%
“…The scale of the observed deficits was equivalent to an average 10-year decline in global performance between the ages of 20 to 70 within this dataset. As a comparison, the authors remarked that this deficit was larger than the mean deficit of 512 people who indicated they had previously suffered a stroke and 1016 who reported learning disabilities [ 101 ]. “Brain fog”, i.e., confusion, forgetfulness, inability to focus, fatigue, and low mental energy [ 102 , 103 ] may be thus an emerging major sequela of COVID-19 infection ( Figure 1 ).…”
Section: Melatonin and Neuroprotectionmentioning
confidence: 99%